The relationship between socioeconomic status and transactional sex among young women in South Africa - Sello, Matshidiso Valeria (My University, 2017)
Introduction: Across Sub-Saharan Africa, studies have shown transactional sex, characterized by the exchange of money or gifts for sex, to be one of the major contributing factors of HIV/AIDS infection. Risky sexual behaviours such as multiple sexual partners, non-condom use and transactional sex are driving forces behind negative health outcomes of young people. Thus, the aim of the study is to determine the association between socio-economic status and transactional sex among young women in South Africa, primarily to investigate whether transactional sex is a survival strategy or not among young women in South Africa. Methods: Secondary data analysis was done from a cross-sectional study conducted in 2012 by the Third National Communication Survey. This analysis was limited to 4 586 167 (weighted) sexually active females aged 16-24 who reported engaging in transactional sex. STATA version 13 was used to analyse this data. Descriptive statistics was used to analyse data at the univariate level. The Chi-squared test was conducted to test the relationship between the outcome variable and the independent variables. The complementary log-log regression model was used to analyse the data at multivariate level to identify the association between demographic factors (age, race, marital status, type of residence and province), socio-economic characteristics (education status or training status and employment status), beliefs towards behaviour, subjective norms towards behaviour and transactional sex. Results: Transactional sex was higher among women whose age at first sex was 18-19 (6.34%) compared to women of older ages 20+ years (0.4%). African women were likely to engage more in transactional sex (3.46%), compared to women of other races (2.48%). This study has found that a relationship between women who were not in Education, Employment and Training (NEETS) and transactional sex did not exist (AOR 1.10, 95% CI: 0.62-1.96). Single women had higher odds of engaging in transactional sex compared to cohabitating women and married women (AOR 1.04, 95% CI: 0.42-2.54). Conclusion: The findings of this study have shown that although transactional sex is a common behaviour among young women in South Africa, there is no relationship between socio economic status and transactional sex. Being NEETS has no association with young women engaging in transactional sex, which means that young women were more likely to engage in transactional sexual relationships for reasons other than survival; that is reasons for having fashionable clothes, cars, expensive holidays, and airtime. However, factors such as early age at first sexual encounter, race, and beliefs about behaviour and subjective norms were associated with transactional sex. The fact that some young women believed that they would not be infected with HIV suggests that there is a need to have intervention programmes to educate young people about HIV risk factors. This study is relevant in informing health policies, planning and programme designs of sexual and reproductive health services in South Africa. Transactional sex is a sensitive issue; problems of underreporting may be expected.
A research report submitted to the School of Social Science, University of the Witwatersrand in partial fulfilment of the Master of Arts in Demography and Population Studies, November 2017
Keywords: Young women--Sexual behavior--South Africa; Young women--South Africa; Sex--Social aspects--South Africa; HIV infections--Transmission--South Africa